TINGKAT PENGETAHUAN DAN SIKAP PENGGUNAAN ANTIBIOTIK DI FASILITAS PELAYANAN KESEHATAN INDONESIA - Dewi, Eva Rosdiyana; Wahyuningsih, Sri (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Inappropriate antibiotic use can lead to bacterial resistance, a serious global issue including in Indonesia. The level of public knowledge and attitudes regarding antibiotic utilization are crucial factors in controlling the occurrence of resistance. This literature review aims to assess the community's level of knowledge and attitudes toward antibiotic use in Indonesia, as well as the influencing factors. The methodology employed is a literature study, with data collected through electronic databases such as Google Scholar, PubMed, and ScienceDirect, using keywords like